INFLUENCE OF SCHOOL PRINCIPAL LEADERSHIP AND WORK DISCIPLINE TOWARDS TEACHER PERFORMANCE - Amiruddin Siahaan; Yusuf Hadi Jaya; Rahmadiah Siregar (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2019)
The data analysistechniques used in description analysis include correlation analysis and regression. The resultsshowed that the school principal's leadership style influenced the teacher's performance by44.5%.These findings give the meaning that 44.5% of teacher performance can be predicted throughthe principal's leadership style. The work discipline affects the teacher's performance by 53.4%. Thesefindings give meaning 31.60% of the teacher's performance can be predicted through work discipline.The leadership style of the school principal and work discipline jointly affects the teacher'sperformance by 63.9% while the remaining 36.1% is derived from the other variables outside of this study.